(untitled) (Journal of Finance, Business and Management Studies, 2021)
This work is aimed at developing an instrumental model of Management Accounting, oriented to Management Control. The current scenarios in which companies operate, globalized, with permanent and vertiginous changes in the environment and technologies, (Digital Age), regulations in the environment establish high competitiveness and short-term operational cycles Organizations establish strategic plans that must be conducted and directed by managers. Accounting information under standards if they have improved the quality of the information, presents significant limitations for management control. Managers need to have information regarding costs, revenues and results attributable to their areas of responsibility. The proposed "Net Profit Chain" model is based on having a decentralized organizational structure in responsibility centers, the application of internal transfer pricing and Accounting by Responsibility Centers, which generates information for the different responsibility centers. The "Net Profit Chain" will allow to know the results of each segmented for the measurement of the performance and economic efficiency of each center, measuring the contribution of each of them in the generation of the net profit or net margin of the company.